Breaking the Cycle of Sinus Suffering: The Role of Homoeopathic Similimum - A Case Report (Advancements in Homeopathic Research, 2025)
A complex inflammatory illness of the nasal  and paranasal mucosae, chronic rhinosinusitis  (CRS) manifests itself in a multitude of symptom  combinations. Conditions ranging from unilateral  single sinus disease to extensive sinonasal  airway inflammation can be classified as chronic  rhinosinusitis. Allopathic medicines are frequently  used to treat acute attack symptoms. Allopathic  medication for sinusitis, however, can be hazardous  if used repeatedly or over an extended period of  time and does not prevent further infections. Long term sinus infections have been shown to respond  effectively to homoeopathy since the patient is treated  individually in this method.
Keywords: Chronic rhinosinusitis; Homoeopathy; Similimum